Reading Lewis Carroll’s Alice’s Adventures in Wonderland through the Surrealist Lenses of Anthony Browne - Sikorska, Magdalena (Porównania, 2016)
The paper analyses Anthony Browne’s illustrations for Alice’s Adventures in Wonderland by Lewis Carroll. Browne’s images, rooted in and indebted to surrealist painting (especially the art of René Magritte), show manifold relations between the formal qualities and social questions of surrealism and Carroll’s novel. In his illustrations Browne employs numerous optical games and illusions to undermine the traditions of the gaze and visual perception, and thus, in a way, he equates the visual methods of surrealism with those used by Carroll in Alice.